Acquired pellicle protein-based engineering protects against erosive demineralization - Carvalho, Thamyris Souza; Araújo, Tamara Teodoro; Ventura, Talita Mendes Oliveira; Dionizio, Aline; Câmara, João Victor Frazão; Moraes, Samanta Mascarenhas; Pelá, Vinicius Taioqui; Martini, Tatiana; Leme, Julia Chaparro; Derbotolli, Ana Luiza Bogaz; Grizzo, Larissa Tercilia; Crusca, Edson [UNESP]; et al. (Elsevier, 2020)
Objectives: To evaluate, in vivo: 1) proteomic alterations in the acquired enamel pellicle (AEP) after treatment with sugarcane-derived cystatin (CaneCPI-5), hemoglobin (HB), statherin-derived peptide (StN15) or their combination before the formation of the AEP and subsequent erosive challenge; 2) the protection of these treatments against erosive demnineralization. Materials and methods: In 5 crossover phases, after prophylaxis, 10 volunteers rinsed (10 mL, 1 min) with: deionized water-1, 0.1 mg/mL CaneCPI-5-2, 1.0 mg/mL HB-3, 1.88 × 10-5 M StN15-4 or their combination-5. AEP was formed (2 h) and enamel biopsy (10 μL, 1%citric acid, pH 2.5, 10 s) was performed on one incisor for calcium analysis. The same acid was applied on the vestibular surfaces of the remaining teeth. The acid-resistant proteins within the remaining AEP were collected. Samples were quantitatively analyzed by label-free proteomics. Results: Treatment with the proteins/peptide, isolated or combined, increased several acid-resistant proteins in the AEP, compared with control. The highest increases were seen for PRPs (32-fold, StN15), profilin (15-fold, combination), alpha-amylase (9-fold; StN15), keratins (8-fold, CaneCPI-5 and HB), Histatin-1 (7-fold, StN15), immunoglobulins (6.5-fold, StN15), lactotransferrin (4-fold, CaneCPI-5), cystatins, lysozyme, protein S-100-A9 and actins (3.5-fold, StN15), serum albumin (3.5-fold, CaneCPI-5 and HB) and hemoglobin (3-fold, StN15). Annexin, calmodulin, keratin, tubulin and cystatins were identified exclusively upon treatment with the proteins/peptide, alone or combined. Groups 2, 3 and 4 had significantly lower Ca released from enamel compared to group 1 (Kruskal-Wallis/Dunn's, p < 0.05). Conclusions: Treatment with CaneCPI-5, HB or StN15 remarkably increases acid-resistant proteins in the AEP, protecting against erosion. Clinical significance: Our results show, for the first time, that treatment with proteins/peptide remarkably increases acid-resistant proteins in the AEP, protecting against erosive demineralization. These findings open an avenue for a new preventive approach for erosive demineralization, employing acquired pellicle engineering procedures that may in the future be incorporated into dental products.
Keywords: Acquired enamel pellicle; Cystatin; Dental erosion; Hemoglobin; Proteomics; Statherin